Method for designing mix proportion of magnesium grouting reinforcement slurry
Through the design method of magnesium-based grouting reinforced slurry mix ratio, activated magnesium oxide is used to promote cement hydration reaction, improve the early strength and cohesion of composite foundations, solve the problem of poor reinforcement effect of silt soft soil layer, and achieve efficient, environmentally friendly and economical reinforcement effect.
Patent Information
- Application Number
- CN202411854299.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-17
AI Technical Summary
On the premise of meeting existing specifications and technical parameters, how to determine a slurry mix ratio that can effectively reinforce the silt soft soil layer must not only ensure good reinforcement effect, but also have strong economicality and environmental protection.
The magnesium-based grouting reinforced slurry mix ratio design method is used. By taking silt soil, cement and activated magnesium oxide as raw materials, the natural moisture content of the original soil is measured and dried, the incorporation ratio of different cement and activated magnesium oxide is determined, the slurry is configured and stirred evenly, standard samples are formed for curing and compressive tests, and the slurry mix ratio is optimized.
Through the incorporation of activated magnesium oxide, the hydration reaction of cement is promoted, the early strength of the composite foundation is improved, the cohesion and internal friction wing parameters are increased, the bearing capacity of the roadbed is improved, the overall settlement is reduced, the stability of the composite foundation is ensured, and the advantages of environmental protection, pollution-free, and saving construction period are also advantageous.
Smart Images

Figure CN119724412A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of highway construction, and in particular to a method for designing a mix ratio of a magnesium-based grouting reinforcement slurry. Background Art
[0002] The plain areas in the middle and lower reaches of the Yangtze River are densely covered with lakes, with a well-developed water system and a high groundwater level. Due to the impact and sedimentation of river water, silt sand soft soil layers are widely distributed along the river. The silt sand layers have the characteristics of high groundwater levels, large burial depths, thick covering layers, low bearing capacity and easy liquefaction.
[0003] Generally, soft soil grouting treatment technology uses soft soil as a solidifying substrate to solve the problem of environmental pollution. It is a recognized construction treatment measure that is technically feasible, environmentally friendly, and economically efficient. The slurry mix ratio is an important factor affecting the effect and economy of highway soft foundation reinforcement. Therefore, the purpose of cement-based grouting reinforcement slurry mix ratio design is to determine the slurry mix ratio with good reinforcement effect, strong economy, and environmental protection under the premise of meeting existing specifications and technical parameters. Summary of the invention
[0004] The purpose of the present invention is to provide a method for designing a slurry mix ratio for magnesium-based grouting reinforcement. The technical problem solved by the present invention is to determine a slurry mix ratio with good reinforcement effect, strong economy and environmental protection under the premise of meeting existing specifications and technical parameters.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for designing a magnesium-based grouting reinforcement slurry mix ratio comprises the following steps:
[0007] Take the silt material, cement and activated magnesium oxide of the original soil as raw materials, first determine the natural moisture content of the original silt soil, then dry the original soil at a constant temperature of 60-70°C for 6-8h, grind the dried soil after drying and pass it through a 0.5mm sieve to obtain air-dried soil, and measure the moisture content of the air-dried soil;
[0008] Determine three different cement mixing ratios, the three different cement mixing ratios are 3-9% of the original soil mass respectively;
[0009] Select active magnesium oxide with a purity of not less than 95% and add it in a ratio of 2-4% of the cement mass; prepare three slurries with different cement addition ratios, and the three slurries with different cement addition ratios all meet the conditions of slurry fluidity;
[0010] In the process of making slurry, firstly, mix cement and air-dried soil evenly, then stir active magnesium oxide and water evenly to prepare gelling liquid, add gelling liquid all at once or gradually, start stirring from the time of adding gelling liquid until it is evenly stirred, the stirring time is not less than 5 minutes, after stirring evenly, put the mixture into the test mold to form, and prepare the standard sample;
[0011] The samples were placed in a standard curing box for curing in accordance with the specifications. The slurry samples with three different cement addition ratios were subjected to three unconfined compression tests and triaxial shear tests at the age of 7-28 days.
[0012] As a further solution of the present invention: original soil: cement: active magnesium oxide = 100:3:3.
[0013] As a further solution of the present invention: the water-to-binder ratio is 1:1.
[0014] As a further solution of the present invention: the unconfined test specimen is a cylindrical specimen with a diameter and a height of 39.1 mm and 80 mm respectively, and the triaxial test specimen is a cylindrical specimen with a diameter of 39.1 mm and a height of 80 mm.
[0015] As a further solution of the present invention: the sample should be demoulded after standing for 48 hours, and the test piece should be cured in water in a standard curing box, the interval between the test pieces should not be less than 10 mm, and the water surface should not be less than 20 mm above the surface of the test piece.
[0016] As a further solution of the present invention, three slurries with different cement mixing ratios are prepared, and the specific process is as follows:
[0017] Obtaining physical property data of the active magnesium oxide; wherein the physical property data includes the particle size of the active magnesium oxide,
[0018] The particle size data of each group of active magnesium oxide samples were analyzed to obtain the total activity impact factor of active magnesium oxide incorporation;
[0019] Based on the total activity impact factor of active magnesium oxide incorporation, the compensation coefficient was calculated;
[0020] The compensation coefficient and the stirring speed preset in the process are obtained, and the stirring speed preset in the process is multiplied by the compensation coefficient to obtain the stirring speed increase.
[0021] As a further solution of the present invention: the proportion influence factor of the low-activity target of each group of active magnesium oxide samples is multiplied by the difference influence factor of the low-activity target to obtain the activity influence factor of each group of active magnesium oxide samples; the activity influence factors of all groups of active magnesium oxide samples are averaged to obtain the activity influence factor of the active magnesium oxide samples; and the total activity influence factor of the active magnesium oxide incorporation is calculated by the formula, which is as follows:
[0022]
[0023] Among them, XZ is the total activity influence factor of active magnesium oxide incorporation, mz is the total mass of active magnesium oxide incorporation, my is the total mass of each group of active magnesium oxide samples, and Xy is the activity influence factor of the active magnesium oxide sample.
[0024] As a further solution of the present invention: the process of obtaining the influencing factor of the low-activity target is:
[0025] The particle size data of each group of active magnesium oxide samples are used for feature recognition, and active magnesium oxide targets with a particle size larger than the standard are extracted and marked as low-activity targets; active magnesium oxide targets with a particle size equal to the standard are extracted and marked as normal-activity targets; active magnesium oxide targets with a particle size smaller than the standard are extracted and marked as high-activity targets;
[0026] The particle size statistics of low-activity targets, normal-activity targets, and high-activity targets are calculated, and the influence factor of the proportion of low-activity targets is obtained by formula. The specific formula is as follows:
[0027]
[0028] In formula (1), Xd is the impact factor of the low-activity target, a = 1, 2, ..., i, is the number of low-activity targets, wd i is the particle size of the i-th low-activity target; b = 1, 2, ..., j, is the number of low-activity targets, wd j is the particle size of the jth normally active target; c = 1, 2, ..., k, is the number of low-activity targets, wd k is the particle size of the kth normally active target.
[0029] As a further solution of the present invention: the process of obtaining the differential influencing factors of low-activity targets is:
[0030] The differential impact factor of low-activity targets is calculated by the formula, which is as follows:
[0031]
[0032] In formula (2), Xc is the differential impact factor of low-activity targets, a=1,2,...,i, is the number of low-activity targets, wd i is the particle size of the i-th low-activity target, and wdb is the active magnesium oxide target with a standard particle size.
[0033] As a further solution of the present invention: the process of obtaining the compensation coefficient is:
[0034] When the total activity impact factor of active magnesium oxide incorporation is obtained, the compensation coefficient is calculated by the formula, and the specific formula is as follows:
[0035]
[0036] Among them, XM is the compensation coefficient, XZ is the total activity influencing factor of active magnesium oxide incorporation, mz is the total mass of active magnesium oxide incorporation, and wdb is the active magnesium oxide target with a standard particle size.
[0037] Beneficial effects of the present invention:
[0038] The addition of active magnesium oxide in the present invention promotes the hydration reaction of cement, improves the early strength of the composite foundation, and promotes the next construction process; the active magnesium oxide-cement composite slurry can significantly increase the cohesion and internal friction angle mechanical parameters of the composite foundation soil, improve the bearing capacity of the roadbed, reduce the overall settlement of the roadbed, and ensure the stability of the composite foundation; the expansion of magnesium hydroxide crystals generated by the hydration reaction of active magnesium oxide compensates for the shrinkage caused by cement hardening, and solves the problem of associated voids generated by cement slurry reinforcement of soft foundation; the active magnesium oxide-cement composite slurry and the reinforced body can form an overall composite foundation with higher strength, which is significantly different from the traditional composite foundation replacement treatment and has the advantages of environmental protection, no pollution, and saving construction time; the raw materials of the composite slurry are widely available, low in price, have good economic benefits, and can save a lot of engineering funds; the composite foundation formed by the slurry treatment of soft foundation has higher bearing capacity, eliminates liquefaction phenomenon, and can meet the bearing capacity requirements of highway foundation;
[0039] The present invention controls the stirring speed by detecting the activity of the active magnesium oxide, judging the effective proportion of the mass of the active magnesium oxide and the activity proportion of the active magnesium oxide, so that the adjusted stirring speed can increase the shear force on the active magnesium oxide, thereby increasing the particle size of the active magnesium oxide to improve the activity of the active magnesium oxide, thereby making the quality and activity of the added active magnesium oxide meet the requirements of cement fluidity. Finally, the slurry not only has fluidity that meets the process standard, but also can improve the activity requirements of the active magnesium oxide, promote the hydration reaction of the cement, and improve the early strength of the composite foundation. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0041] Figure 1 It is a schematic diagram of the process framework structure of the present invention;
[0042] Figure 2 It is the unconfined compressive strength table of the sample when the active magnesium oxide incorporation ratio is 2%;
[0043] Figure 3 It is the unconfined compressive strength table of the sample when the active magnesium oxide incorporation ratio is 3%;
[0044] Figure 4 It is the unconfined compressive strength table of the sample when the active magnesium oxide incorporation ratio is 4%;
[0045] Figure 5 It is a table of internal friction angle and cohesion values after fitting of triaxial test. DETAILED DESCRIPTION
[0046] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0047] Embodiment 1
[0048] like Figure 1 As shown, a magnesium-based grouting reinforcement slurry mix ratio design method provided by an embodiment of the present invention comprises the following steps:
[0049] A. Take the silt material, cement and activated magnesium oxide of the original soil as raw materials, first determine the natural moisture content of the original silt soil, then dry the original soil at a constant temperature of 60-70℃ for 6-8h, grind the dried soil and pass it through a 0.5mm sieve to obtain air-dried soil, and measure the moisture content of the air-dried soil;
[0050] B. Determine three different cement mixing ratios, each of which is 3% of the original soil mass;
[0051] C. Select a water-binder ratio of 1:1 and an active magnesium oxide with a purity of not less than 95% to be added at a ratio of 2% of the cement mass;
[0052] D. Prepare three slurries with different cement mixing ratios, and all three slurries with different cement mixing ratios meet the condition of good slurry fluidity. In the process of making the slurry, first mix the cement and air-dried soil evenly, then stir the active magnesium oxide and water evenly to prepare the gelling liquid, add the gelling liquid once or gradually, and stir from the time of adding the gelling liquid until it is evenly stirred, and the stirring time is not less than 5 minutes. After stirring evenly, put the mixture into the test mold to form it, and prepare the standard sample;
[0053] E. The samples were placed in the water of a standard curing box for curing according to the specification requirements. The slurry samples with three different cement mixing ratios were subjected to three unconfined compression tests and triaxial shear tests at the ages of 7d, 14d and 28d respectively;
[0054] F. According to the analysis of the test results of the unconfined compression test and the triaxial shear test, active magnesium oxide effectively improves the strength of cement-stabilized soil, and effectively improves the cohesion and internal friction angle mechanical parameters of cement-stabilized soil; similarly, with the continuous increase of cement incorporation ratio, the unconfined compressive strength of the sample continues to increase, and the unconfined compressive strength of the sample (including cohesion and internal friction angle mechanical parameters) increases with the extension of age; with the increase of active magnesium oxide incorporation ratio, the unconfined compressive strength of the sample with the same cement incorporation ratio first increases and then decreases, especially when the change is more obvious at the age of 28d. The cohesion when the active magnesium oxide incorporation ratio is 3% increases by as much as 37.4% compared with the cohesion when the active magnesium oxide incorporation ratio is 2%. The results of the test design all meet the foundation design strength requirements. Therefore, according to the test results and engineering economic requirements, a scheme with a cement incorporation ratio of 3% and an active magnesium oxide incorporation ratio of 3% was adopted, that is, the final design quality mix ratio was selected as: original soil: cement: active magnesium oxide = 100:3:3, and the water-cement ratio was 1:1.
[0055] The unconfined test specimens are cylindrical specimens with a diameter and height of 39.1mm and 80mm respectively. The triaxial test specimens are cylindrical specimens with a diameter of 39.1mm and a height of 80mm. All specimens should be demoulded after standing for 48 hours. The specimens should be cured in water in a standard curing box. The interval between specimens should not be less than 10mm, and the water level should not be less than 20mm above the specimen surface.
[0056] Embodiment 2
[0057] The difference from the first embodiment is that:
[0058] B. Determine three different cement mixing ratios, the three different cement mixing ratios are 3%-9% of the original soil mass respectively;
[0059] C. Select a water-cement ratio of 1:1, and the active magnesium oxide with a purity of not less than 95% is added in an amount of 2%-4% of the cement mass.
[0060] Embodiment 3
[0061] The difference from the first embodiment is that:
[0062] B. Determine three different cement mixing ratios, the three different cement mixing ratios are 3%-9% of the original soil mass respectively;
[0063] C. Select a water-cement ratio of 1:1 and an active magnesium oxide with a purity of not less than 95% in the ratio of 2% to 4% of the cement mass.
[0064] Embodiment 4
[0065] On the basis of Examples 1 to 3, whether the slurry fluidity meets the conditions is the primary factor for the quality inspection of the standard sample. If its fluidity does not meet the requirements, it will have a greater impact on the quality of the cement. In addition, it is currently impossible to determine the different activity levels of the activated magnesium oxide, so that if it is still carried out according to the original standard, it will affect the hydration reaction of the activated magnesium oxide cement.
[0066] Step 1: Obtaining physical property data of active magnesium oxide;
[0067] Among them, the physical property data include the particle size of the activated magnesium oxide;
[0068] Specifically, before the active magnesium oxide is added, multiple groups of active magnesium oxide samples of the same weight are obtained by random sampling;
[0069] Obtaining particle size data of each group of active magnesium oxide samples, wherein the particle size data includes the particle size of the active magnesium oxide;
[0070] Scanning electron microscopy (SEM) is a high-resolution microscope that can be used to observe the morphology and size of particles. Through SEM, the particle size of active magnesium oxide particles can be directly observed;
[0071] Step 2: Analyze the particle size data of each group of active magnesium oxide samples to obtain the total activity impact factor of active magnesium oxide incorporation;
[0072] Specifically, the particle size data of each group of active magnesium oxide samples are subjected to feature recognition, active magnesium oxide targets with a particle size larger than the standard particle size are extracted, and the active magnesium oxide targets are marked as low-activity targets, active magnesium oxide targets with a particle size equal to the standard particle size are extracted, and the active magnesium oxide targets are marked as normal-activity targets, and active magnesium oxide targets with a particle size smaller than the standard particle size are extracted, and the active magnesium oxide targets are marked as high-activity targets;
[0073] The particle size statistics of low-activity targets, normal-activity targets, and high-activity targets are calculated, and the influence factor of the proportion of low-activity targets is obtained by formula. The specific formula is as follows:
[0074]
[0075] In formula (1), Xd is the impact factor of the low-activity target, a = 1, 2, ..., i, is the number of low-activity targets, wd i is the particle size of the i-th low-activity target; b = 1, 2, ..., j, is the number of low-activity targets, wd jis the particle size of the jth normally active target; c = 1, 2, ..., k, is the number of low-activity targets, wd k is the particle size of the kth normally active target;
[0076] More specifically, we continue to analyze low-activity targets and calculate the differential impact factor of low-activity targets through the formula. The formula is as follows:
[0077]
[0078] In formula (2), Xc is the differential impact factor of low-activity targets, a=1,2,...,i, is the number of low-activity targets, wd i is the particle size of the i-th low-activity target, and wdb is the active magnesium oxide target with a standard particle size;
[0079] The product of the proportion influence factor of the low-activity target of each group of active magnesium oxide samples and the difference influence factor of the low-activity target is calculated to obtain the activity influence factor of each group of active magnesium oxide samples; then the activity influence factors of all groups of active magnesium oxide samples are averaged to obtain the activity influence factor of the active magnesium oxide samples; and then the total activity influence factor of active magnesium oxide incorporation is calculated by the formula, which is as follows:
[0080]
[0081] In formula (3), XZ is the total activity impact factor of active magnesium oxide incorporation, mz is the total mass of active magnesium oxide incorporation, my is the total mass of each group of active magnesium oxide samples, and Xy is the activity impact factor of active magnesium oxide samples;
[0082] Step 3: Calculate the compensation coefficient based on the total activity impact factor of active magnesium oxide incorporation;
[0083] Specifically, when the total activity impact factor of active magnesium oxide incorporation is obtained, the compensation coefficient is calculated by the formula, and the specific formula is as follows:
[0084]
[0085] In formula (4), XM is the compensation coefficient, XZ is the total activity influencing factor of active magnesium oxide incorporation, mz is the total mass of active magnesium oxide incorporation, and wdb is the target active magnesium oxide of standard particle size;
[0086] Step 4: Obtain the compensation coefficient and the stirring speed preset in the process, and multiply the stirring speed preset in the process by the compensation coefficient to obtain the stirring speed increase;
[0087] The obtained stirring speed increase is sent to a stirrer for controlling the stirring of the slurry, so that the stirrer increases the stirring speed by a corresponding stirring speed increase on the stirring speed preset in the process;
[0088] The technical solution of the embodiment of the present invention is as follows: by detecting the activity of activated magnesium oxide, the effective proportion of the mass of activated magnesium oxide and the activity proportion of the activated magnesium oxide are determined to control the stirring speed, so that the adjusted stirring speed can increase the shear force on the activated magnesium oxide, thereby increasing the particle size of the activated magnesium oxide to improve the activity of the activated magnesium oxide, thereby making the quality and activity of the added activated magnesium oxide meet the requirements of cement fluidity. Finally, the slurry not only has fluidity that meets the process standards, but also can improve the activity requirements of the activated magnesium oxide, promote the hydration reaction of the cement, and improve the early strength of the composite foundation.
[0089] The working principle of the present invention is as follows: Figure 2-5As shown, the present invention forms a composite foundation that meets the standard bearing capacity requirements through a series of physical and chemical reactions between the curing materials cement, active magnesium oxide and the reinforced silt sand. The main curing effects are as follows: after the slurry is injected into the cement soil, as the curing cycle increases, the grouting material continuously undergoes hydration reaction and carbonization reaction, accompanied by the continuous precipitation of gelling substances, and at the same time, the chemical reaction of the active magnesium oxide produces volume expansion. The flaky crystals generated in this process form an embedded skeleton with the original crystals after the ion exchange chemical reaction, which makes up for the associated pore problem caused by the hardening of the cement soil, thereby making the soil structure dense, and the crystal products after the chemical reaction combine with the soil to form a composite, thereby enhancing the bearing capacity of the roadbed, and then forming a high-strength and low-compressibility composite foundation that meets the strength requirements of the roadbed in the silt sand layer, thereby achieving the effect of reinforcing the soft foundation. The unconfined compression test is the main method of strength inspection standards in engineering, and the test procedures are mature and the operation is highly standardized. By summarizing the test, the influence of the composite slurry mix ratio on the trial curing strength is discussed; the triaxial test is an engineering method to determine the shear strength of the soil The influence of the grouting slurry mix ratio on the shear strength parameters cohesion and internal friction angle was discussed by summarizing the test results. According to the test results, the active magnesium oxide effectively improved the strength of cement-solidified soil, and effectively improved the mechanical parameters of cohesion and internal friction angle of cement-solidified soil; similarly, with the continuous increase of cement incorporation ratio, the unconfined compressive strength of the sample increased continuously, and the unconfined compressive strength of the sample (including mechanical parameters of cohesion and internal friction angle) increased with the extension of age; and with the addition of active magnesium oxide, the unconfined compressive strength of the sample increased with the increase of age. With the increase of cement incorporation ratio, the unconfined compressive strength of the specimens with the same cement incorporation ratio first increases and then decreases, especially when the change is more obvious at the age of 28 days. The cohesion when the active magnesium oxide incorporation ratio is 3% increases by 37.4% compared with the cohesion when the active magnesium oxide incorporation ratio is 2%. In addition, the experimental design results of cement incorporation ratios of 3% to 9% and active magnesium oxide incorporation ratios of 2% to 4% all meet the foundation design strength requirements. Therefore, according to the test results and engineering economic requirements, a scheme with a cement incorporation ratio of 3% and an active magnesium oxide incorporation ratio of 3% and 3% was adopted.
[0090] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for designing the proportion of magnesium-based grouting reinforcement slurry, characterized in that: The following steps are involved: Take the silt material, cement and activated magnesium oxide of the original soil as raw materials, first determine the natural moisture content of the original silt soil, then dry the original soil at a constant temperature of 60-70°C for 6-8h, grind the dried soil after drying and pass it through a 0.5mm sieve to obtain air-dried soil, and measure the moisture content of the air-dried soil; Determine three different cement mixing ratios, the three different cement mixing ratios are 3-9% of the original soil mass respectively; Select active magnesium oxide with a purity of not less than 95% and add it in a ratio of 2-4% of the cement mass; prepare three slurries with different cement addition ratios, and the three slurries with different cement addition ratios all meet the conditions of slurry fluidity; In the process of making slurry, firstly, mix cement and air-dried soil evenly, then stir active magnesium oxide and water evenly to prepare gelling liquid, add gelling liquid all at once or gradually, start stirring from the time of adding gelling liquid until it is evenly stirred, the stirring time is not less than 5 minutes, after stirring evenly, put the mixture into the test mold to form, and prepare standard specimen; The samples were placed in a standard curing box for curing in accordance with the specifications. The slurry samples with three different cement addition ratios were subjected to three unconfined compression tests and triaxial shear tests at the age of 7-28 days.
2. A magnesium-based grouting reinforcement slurry mix design method according to claim 1, characterized in that: Original soil: cement: activated magnesium oxide = 100:3:
3.
3. A magnesium-based grouting reinforcement slurry mix design method according to claim 1, characterized in that: The water-to-glue ratio is 1:
1.
4. A magnesium-based grouting reinforcement slurry mix design method according to claim 1, characterized in that: The unconfined test specimens are cylindrical specimens with diameter and height of 39.1 mm and 80 mm respectively, and the triaxial test specimens are cylindrical specimens with diameter of 39.1 mm and height of 80 mm.
5. A magnesium-based grouting reinforcement slurry mix design method according to claim 1, characterized in that: The sample should be demoulded after standing for 48 hours and the specimen should be cured in water in a standard curing box. The interval between specimens should not be less than 10mm and the water level should not be less than 20mm above the specimen surface.
6. A magnesium-based grouting reinforcement slurry mix design method according to claim 1, characterized in that: Three slurries with different cement mixing ratios were prepared. The specific process is as follows: Obtaining physical property data of the active magnesium oxide; wherein the physical property data includes the particle size of the active magnesium oxide, The particle size data of each group of active magnesium oxide samples were analyzed to obtain the total activity impact factor of active magnesium oxide incorporation; Based on the total activity impact factor of active magnesium oxide incorporation, the compensation coefficient was calculated; The compensation coefficient and the stirring speed preset in the process are obtained, and the stirring speed preset in the process is multiplied by the compensation coefficient to obtain the stirring speed increase.
7. A magnesium-based grouting reinforcement slurry mix design method according to claim 6, characterized in that: The product of the proportion influence factor of the low-activity target of each group of active magnesium oxide samples and the difference influence factor of the low-activity target is calculated to obtain the activity influence factor of each group of active magnesium oxide samples; then the activity influence factors of all groups of active magnesium oxide samples are averaged to obtain the activity influence factor of the active magnesium oxide samples; and then the total activity influence factor of active magnesium oxide incorporation is calculated by the formula, which is as follows: Among them, XZ is the total activity influence factor of active magnesium oxide incorporation, mz is the total mass of active magnesium oxide incorporation, my is the total mass of each group of active magnesium oxide samples, and Xy is the activity influence factor of the active magnesium oxide sample.
8. A magnesium-based grouting reinforcement slurry mix design method according to claim 7, characterized in that: The process of obtaining the impact factor of low-activity targets is as follows: The particle size data of each group of active magnesium oxide samples are used for feature recognition, and active magnesium oxide targets with a particle size larger than the standard are extracted and marked as low-activity targets; active magnesium oxide targets with a particle size equal to the standard are extracted and marked as normal-activity targets; active magnesium oxide targets with a particle size smaller than the standard are extracted and marked as high-activity targets; The particle size statistics of low-activity targets, normal-activity targets, and high-activity targets are calculated, and the influence factor of the proportion of low-activity targets is obtained by formula. The specific formula is as follows: In formula (1), Xd is the impact factor of the low-activity target, a = 1, 2, ..., i, is the number of low-activity targets, wd i is the particle size of the i-th low-activity target; b = 1, 2, ..., j, is the number of low-activity targets, wd j is the particle size of the jth normally active target; c = 1, 2, ..., k, is the number of low-activity targets, wd k is the particle size of the kth normally active target.
9. A magnesium-based grouting reinforcement slurry mix design method according to claim 8, characterized in that: The process of obtaining the differential impact factors of low-activity targets is as follows: The differential impact factor of low-activity targets is calculated by the formula, which is as follows: In formula (2), Xc is the differential impact factor of low-activity targets, a=1,2,...,i, is the number of low-activity targets, wd i is the particle size of the i-th low-activity target, and wdb is the active magnesium oxide target with a standard particle size.
10. A magnesium-based grouting reinforcement slurry mix design method according to claim 9, characterized in that: The process of obtaining the compensation coefficient is: When the total activity impact factor of active magnesium oxide incorporation is obtained, the compensation coefficient is calculated by the formula, and the specific formula is as follows: Among them, XM is the compensation coefficient, XZ is the total activity influencing factor of active magnesium oxide incorporation, mz is the total mass of active magnesium oxide incorporation, and wdb is the active magnesium oxide target with a standard particle size.
Citation Information
Patent Citations
Novel mix proportion design method for composite grouting slurry
CN111116106A
Glass fiber reinforced hydrated magnesium silicate cement composite material and preparation method thereof
CN115716742A
Rice hull ash basic magnesium sulfate cement material, cement and mechanical property prediction method thereof
CN116768509A
Method for designing mix proportion of modified biomass ash-magnesium phosphate cement composite material
CN116947451A
Design method for quantifying mix proportion of full-machine-made sand concrete
CN119066294A